Patients' and Physicians' Experience With and Acceptability of a Telemedicine Cabin: Mixed Methods Study - Caroline Villela Galvão de França; Paola Boaro Segalla; Felipe Sebastião de Assis Reis; José Ricardo Silveira Pereira; Alexandre Oliveira de Mattos; Roberta de Moura Ferron; Cleyton Zanardo de Oliveira; Jéssica Bassani Borges; Lilian Quintal Hoffmann; Edmundo Di Giaimo Caboclo (JMIR Human Factors)
Abstract BackgroundTelemedicine represents an essential tool with the potential to reduce health costs, thus avoiding patient displacement and improving patient care outcomes, positioning it as a significant social technology. ObjectiveThis study aims to analyze the implementation of a telehealth cabin at BP Hospital (A Beneficência Portuguesa de São Paulo), focusing on the evaluation of the experiences of both patients and health care professionals, as well as the acceptability of this tool. MethodsA mixed methods study was conducted with 229 participants, divided into 2 phases. The first phase involved 40 apparently healthy individuals to assess the usability, experience, and satisfaction of this group for the later safe application in the group with clinical complaints. The second phase included 189 participants, with complaints to assess the usability, experience, and satisfaction of patients and doctors. In both phases, participants completed screening questionnaires (to assess the eligibility criteria), a socioeconomic demographic questionnaire before using the cabin, and a questionnaire including the System Usability Scale and the Net Promoter Score (NPS) after using the cabin. ResultsThe data analysis of the first phase showed high acceptance of the telehealth cabin, which supported the progression to the second phase. In the second phase, a high usability score was observed among participants with clinical complaints (mean System Usability Scale score of 85.97, SD 15.50) and a high favorability rating (NPS score of 9.4). Health care professionals also reported favorable results, with a usability score of 67.8 and an NPS of 8.0. ConclusionsThe results of this study reinforce the potential for scaling up this practice based on usability outcomes, and highlight its relevance for the development of public policies aimed at expanding access to quality health care in Brazil. This approach improves the interaction of patients with the health care system, while providing professionals with an extended view of clinical conditions through integrated devices, particularly in areas with limited access to medical care.